2018
DOI: 10.1017/s1041610217002873
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of resilience factors in geriatric depression

Abstract: Resilience was significantly associated with a range of mental health constructs in a sample of older adults with depression. Future clinical trials and dismantling studies may help determine whether interventions targeting grit, active coping, accommodative coping, and spirituality can increase resilience and help prevent and treat depression in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 75 publications
6
68
0
Order By: Relevance
“…Furthermore, the authors found that a 1-unit (25% increase) on an item indicating use of cognitive restructuring (ie, "I try to see the humorous side of things when I am faced with problems") was associated with a 125% increase in the odds of PTSD improvement. As this item loaded most strongly on the accommodative coping self-efficacy factor in our recent EFA, 32 this is consistent with our finding that accommodative coping self-efficacy was uniquely predictive of treatment response in our sample.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, the authors found that a 1-unit (25% increase) on an item indicating use of cognitive restructuring (ie, "I try to see the humorous side of things when I am faced with problems") was associated with a 125% increase in the odds of PTSD improvement. As this item loaded most strongly on the accommodative coping self-efficacy factor in our recent EFA, 32 this is consistent with our finding that accommodative coping self-efficacy was uniquely predictive of treatment response in our sample.…”
Section: Discussionsupporting
confidence: 91%
“…Responses are summed with possible total scores ranging from 0 to 100; higher scores indicate greater resilience. Resilience factors identified in the abovementioned EFA (with example items) are (1) grit (eg, “I have a strong sense of purpose”), (2) active coping self‐efficacy (eg, “I am in control of my life”), (3) accommodative coping self‐efficacy (eg, “I am able to adapt to change”), and (4) spirituality (eg, “I believe things happen for a reason”). A reliability analysis (with each item included only in the factor on which it loaded most strongly) using data from the larger EFA sample (N = 337) yielded the following Cronbach α estimates: total CD‐RISC: 0.92, factor 1: 0.89, factor 2: 0.91, factor 3: 0.90, factor 4: 0.71.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations